2003
DOI: 10.1623/hysj.48.3.427.45287
|View full text |Cite
|
Sign up to set email alerts
|

Flow duration curve estimation in ephemeral catchments in Portugal

Abstract: The flow regime of a river can be described using the flow duration curve (FDC), which represents the frequency distribution of flows and can be derived from gauged data. Many resource assessments are required where gauged data are limited or unavailable, thus models for predicting FDCs in ungauged catchments are required. In semiarid environments, such as parts of southern Portugal, river flows often become zero for significant periods of time. This makes modelling the discontinuities in the flow regime using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 11 publications
(13 reference statements)
3
64
0
5
Order By: Relevance
“…To solve this problem, Haan (1977, in Crocker et al 2003 suggested the use of the total probability theorem, according to which the probability of an event A, belonging to the sample space S consisting of K mutually and collectively exclusive events B i , with i ≤ K, is given by:…”
Section: Construction Of Fdcs Using the Total Probability Theoremmentioning
confidence: 99%
“…To solve this problem, Haan (1977, in Crocker et al 2003 suggested the use of the total probability theorem, according to which the probability of an event A, belonging to the sample space S consisting of K mutually and collectively exclusive events B i , with i ≤ K, is given by:…”
Section: Construction Of Fdcs Using the Total Probability Theoremmentioning
confidence: 99%
“…Ganora et al (2009) observed that theoretically FDC could not be interpreted as a probability curve since discharge is correlated between successive time intervals and discharge characteristics are dependent on the season. However the FDC is often interpreted as probability distribution and the most used distribution is the log-normal, which has been proposed by Beard (1943) and successfully used by several authors (Fennessey and Vogel, 1990). Other authors used different distributions as the beta (Iacobellis, 2008) or the kappa (Castellarin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Often these studies regard large catchments with perennial streamflows, as Canada (Leboutillier and Waylen, 1993), India (Singh et al, 2001), Italy (Castellarin et al, 2007Castellarin et al, 2004;Franchini and Suppo, 1996;Iacobellis, 2008;Ganora et al, 2009), Greece (Niadas, 2005), Taiwan (Yu et al, 2002), Philippines (Quimpo et al, 1983), South Africa (Smakhtin et al, 1997) and United States (Fennessey and Vogel, 1990). It is important to point out that analysis of FDC for small catchments with ephemeral streamflows, as in Portugal (Croker et al, 2003) are less frequent than studies for perennial streamflows. Nevertheless small catchments are often of great interest for the development of local water resources especially when exploited by diversions to integrate larger water management systems.…”
Section: Introductionmentioning
confidence: 99%
“…Bu amaçla maksimum yağışların değişimi incelenebildiği [8] gibi, debilerin değişimi de incelenebilmektedir. Kanada [9], Yunanistan [10], Hindistan [11], İtalya [12], Tayvan [13], Filipinler [3], Portekiz [14], Güney Afrika [15], Amerika [16] …”
Section: Gi̇ri̇ş (Introduction)unclassified